THE CHALLENGING OF ELEMENTARY SCHOOL STUDENTS FACING OFFLINE LEARNING IN THE POST COVID-19 - Marsini; Lilik Purwaningsih; Rohana Ahmad (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
The effectiveness of offline and face-to-face learning provides behavioral changes, its has been reduce during COVID-19 Pandemic. However, this study aimed to look at the challenges of elementary school students in dealing with offline learning after COVID-19 Pandemic. A literature review was used as secondary data in this research method. The data consists of social media, electronic media, and journals from May to June 2022. The analysis technique uses the NVivo 12 plus data processing application, a qualitative document analysis tool with computer assistance. The findings show that the most dominant offline learning challenges after the COVID-19 pandemic are excessive dependence on the internet (35.71%), decreased levels of intellectual and emotional intelligence (28.57%), two-way communication between teachers and students who are lacking (21.43%) and comfort online learning (14.29%). The implications of this research are increasing the literacy of school students, where students can filter useful information through more effective blended learning methods.